Managers' views of the effects on their service of hosting a cognitive-behavioural anger management group. Issue 1 (5th January 2015) - Rose, Nicola; Rose, John; Stenfert Kroese, Biza; Stimpson, Aimee; MacMahon, Pamela; Jahoda, Andrew; Townson, Julia; Felce, David; Hood, Kerenza; Willner, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how service managers perceive their service prior to, and following the delivery of a cognitive-behavioural therapy (CBT) anger management group for individuals with an intellectual disability. Design/methodology/approach – Telephone interviews were conducted with seven service managers, before and after a CBT group intervention. The interviews were recorded, transcribed and analysed using thematic analysis to identify common and/or contrasting themes. Findings – Before the intervention took place managers observed a lack of consistency in how their staff dealt with challenging incidents and the serious consequences these incidents had for service users as well as staff. They spoke about the importance of multi-disciplinary working and good quality staff selection, support and training. After the group intervention managers commented on a positive "spilling-out effect" whereby the whole organisation was influenced by the intervention, a greater willingness on the part of service users to talk about their problems, and an increased confidence in the staff members who had co-facilitated the group work. Research limitations/implications – The implications of the themes raised are discussed and recommendations for further research are suggested. Originality/value – This research provides a unique contribution of managers' views and insight into how hosting a CBT group intervention impacted on their wider services.